Global Regulator IscR Positively Contributes to Antimonite Resistance and Oxidation in Comamonas testosteroni S44 - Liu, Hongliang; Zhuang, Weiping; Zhang, Shengzhe; Rensing, Christopher; Huang, Jun; Li, Jie; Wang, Gejiao (Frontiers in Molecular Biosciences, 2015)
Antimonial compounds can be found as a toxic contaminant in the environment. Knowledge on mechanisms of microbial Sb oxidation and its role in microbial tolerance are limited. Previously, we found that Comamonas testosteroni S44 was resistant to multiple heavy metals and was able to oxidize the toxic antimonite [Sb(III)] to the much less toxic antimonate [Sb(V)]. In this study, transposon mutagenesis was performed in C. testosteroni S44 to isolate genes responsible for Sb(III) resistance and oxidation. An insertion mutation into iscR, which regulates genes involved in the biosynthesis of Fe-S clusters, generated a strain called iscR-280. This mutant strain was complemented with a plasmid carrying iscR to generate strain iscR-280C. Compared to the wild type S44 and iscR-280C, strain iscR-280 showed lower resistance to Sb(III) and a lower Sb(III) oxidation rate. Strain iscR-280 also showed lower resistance to As(III), Cd(II), Cu(II), and H2O2. In addition, intracellular γ-glutamylcysteine ligase (γ-GCL) activity and glutathione (GSH) content were decreased in the mutated strain iscR-280. Real-time RT-PCR and lacZ fusion expression assay indicated that transcription of iscR and iscS was induced by Sb(III). Results of electrophoretic mobility shift assay (EMSA) and bacterial one-hybrid (B1H) system demonstrated a positive interaction between IscR and its promoter region. The diverse defective phenotypes and various expression patterns suggest a role for IscR in contributing to multi-metal(loid)s resistance and Sb(III) oxidation via Fe-S cluster biogenesis and oxidative stress protection. Bacterial Sb(III) oxidation is a detoxification reaction.